From one sort of reciprocity to another: the specialization of the tasks and functions as a principle of political unity in Plato’s Republic - Helmer, Etienne (Revista Archai, 2025)
Both Aristotle and Plato consider the economic exchange as one of the most basic social link. According to Ar-istotle though, the individual specialization of the tasks and functions Socrates advocates in the Republic in order to inte-grate these economic exchange into a political order, leads to the division of the city instead of unifying it. This article argues, on the contrary, that the city of the Republic owes its unity to the specialization of the tasks and functions. Far from being di-visive, this principle adds a positive political reciprocity to the ambivalent and negative reciprocity Plato sees at work at the level of the economic exchange